2014
DOI: 10.1088/0741-3335/56/3/035004
|View full text |Cite
|
Sign up to set email alerts
|

Microstability analysis of pellet fuelled discharges in MAST

Abstract: Abstract. Reactor grade plasmas are likely to be fuelled by pellet injection. This technique transiently perturbs the profiles, driving the density profile hollow and flattening the edge temperature profile. After the pellet perturbation, the density and temperature profiles relax towards their quasi-steady-state shape. Microinstabilities influence plasma confinement and will play a role in determining the evolution of the profiles in pellet fuelled plasmas. In this paper we present the microstability analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
(39 reference statements)
8
23
0
Order By: Relevance
“…In particular we focus on the effects of pellets on ELM mitigation. This study thus complements the micro-stability survey in the pellet deposition zone [16] which addresses the inter-ELM transport.…”
Section: Introductionmentioning
confidence: 72%
“…In particular we focus on the effects of pellets on ELM mitigation. This study thus complements the micro-stability survey in the pellet deposition zone [16] which addresses the inter-ELM transport.…”
Section: Introductionmentioning
confidence: 72%
“…However the analysis of this important process would require temporarily resolved profile data (or box car analysis) which is outside the scope of this paper. Post pellet plasmas with hollow density profiles were analysed in MAST in references [16,17]. It was found that an inverted density gradient can unfavourably suppress micro-instabilities reducing the core fuelling rate, however, this depends on the actual values of the temperature gradients after the pellet.…”
Section: Fast Time Scale Particle Lossmentioning
confidence: 99%
“…For negative R L / n no such deep investigation has been carried out. In a very recent study about pellet fuelled discharges of MAST [14], the transport properties of the hollow density, transiently driven by pellet injection, have been investigated. This first microstability analysis predicts the stabilization of the modes for negative R L / n , giving significant indications about the behaviour of the plasma in presence of hollow density profiles.…”
Section: Experimental Datamentioning
confidence: 99%